EVALUASI IMPLEMENTASI PELAYANAN INFORMASI OBAT PASIEN RAWAT JALAN DI INSTALASI FARMASI RUMAH SAKIT YOGYAKARTA - Farida Baroroh (Universitas Ahmad Dahlan, 2011)
To support high quality health service in hospital, Pharmacy Installation of Yogyakarta Hospital needs to evaluate implementation of drug information service for outpatient. This study is aimed to identify the realization of drug information service of outpatient implementation of Pharmacy Installation of Yogyakarta Hospital compared to the specified target. This study was carried out by descriptive design using secondary data of Pharmacy Installation programs, interview with a pharmacist was assigned outpatients serving as research subjects, as well as direct observation of drug information service for outpatient. Gap analysis was used to identify the comparison between the realization and specified target. The result of this study of evaluation in drug information service implementation of outpatient showed negative gaps as much as -0.67%. The component information presented included the efficacy of drugs, how to use, the rules of use, duration of drug use, drug side effects, however the components of drug information that is unallowed in Pharmacy Installation of Yogyakarta Hospital how shcedule of drug use and signs toxicity.